A fascia bow traction method for the treatment of unilateral marginal mandibular nerve paralysis after mandibulectomy for head and neck cancer. (December 2022) - Yoshitatsu, Sumiko; Shiraishi, Makiko; Arika, Takumi
Abstract: Background: Unilateral paralysis of the marginal mandibular nerve (UPMMN) after head and neck cancer surgery is a relatively common condition that causes deformity and an asymmetric appearance of the lower lip and impairs the quality of life of patients. We developed a novel fascia grafting method to improve the appearance of the lower lip in patients with UPMMN. Methods: Two fascia strips and a small fascia loop connecting the two strips are used: one is fixed horizontally to pull the lower lip toward the paralyzed side, and the other is fixed in a bow shape at rest to avoid approaching the lateral mandibular margin. When patients smile or open their mouths, the bow-shaped graft straightens, pulling the paralyzed lower lip laterally downward through the small connecting loop. We used this method to treat four patients with UPMMN who had undergone head and neck cancer ablation. The symmetry and movement of the lower lip were assessed using preoperative and postoperative photographs of three poses (at rest, smiling, and opening the mouth). Results: The fascia grafting procedure restored the symmetry of the lower lip at rest and greatly improved symmetrical lower lip movement when smiling and opening the mouth. According to photographic evaluation scores, all patients had poor lower lip symmetry in the three poses before the procedure, whereas after the procedure, three had excellent lower lip symmetry, and one had good lower lip symmetry. There was a significant difference between the scores before and after the surgery. Conclusions: Fascia grafting is easy and minimally invasive, allows patients to generate an almost symmetrical smile, and consequently improves their QOL. This method may be particularly useful when the lateral mandibular bone is resected during cancer surgery, and the defect is reconstructed with metal plates/soft tissue, as the method does not require approaching the lateral mandibular region.